Heat stress acutely activates insulin‐independent glucose transport and 5′‐AMP‐activated protein kinase prior to an increase in HSP72 protein in rat skeletal muscle. Issue 11 (5th November 2015) - Goto, Ayumi; Egawa, Tatsuro; Sakon, Ichika; Oshima, Rieko; Ito, Kanata; Serizawa, Yasuhiro; Sekine, Keiichi; Tsuda, Satoshi; Goto, Katsumasa; Hayashi, Tatsuya
Abstract: Heat stress (HS) stimulates heat shock protein (HSP) 72 mRNA expression, and the period after an increase in HSP72 protein is characterized by enhanced glucose metabolism in skeletal muscle. We have hypothesized that, prior to an increase in the level of HSP72 protein, HS activates glucose metabolism by acutely stimulating 5′‐AMP‐activated protein kinase (AMPK). Rat epitrochlearis muscle was isolated and incubated either with or without HS (42°C) for 10 and 30 min. HS for 30 min led to an increase in the level of Hspa1a and Hspa1b mRNA but did not change the amount of HSP72 protein. However, HS for both 10 and 30 min led to a significant increase in the rate of 3‐ O ‐methyl‐d ‐glucose (3MG) transport, and the stimulatory effect of 3MG transport was completely blocked by cytochalasin B. HS‐stimulated 3MG transport was also inhibited by dorsomorphin but not by wortmannin. HS led to a decrease in the concentration of ATP, phosphocreatine, and glycogen, to an increase in the level of phosphorylation of AMPK α Thr 172, and to an increase in the activity of both AMPK α 1 and AMPK α 2. HS did not affect the phosphorylation status of insulin receptor signaling or Ca 2+ /calmodulin‐dependent protein kinase II. These results suggest that HS acts as a rapid stimulator of insulin‐independent glucose transport, at least in part by stimulating AMPK via decreased energy status. Although further research is warranted, heat treatment of skeletal muscle might be a promising method to promote glucose metabolism acutely. Abstract : Heat stress (HS) acutely stimulated glucose transport prior to an increase in the levels of heat shock protein 72 (HSP72) protein in isolated rat skeletal muscle. HS also led to a decrease in muscle energy status, and to an increase in the activity of 5′‐AMP‐activated protein kinase (AMPK). Heat treatment of skeletal muscle might be a promising method to promote glucose metabolism acutely.